2004
DOI: 10.1162/089976604773135050
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Temporal Interval Entropy of Neuronal Discharge

Abstract: To better understand the role of timing in the function of the nervous system, we have developed a methodology that allows the entropy of neuronal discharge activity to be estimated from a spike train record when it may be assumed that successive interspike intervals are temporally uncorrelated. The so-called interval entropy obtained by this methodology is based on an implicit enumeration of all possible spike trains that are statistically indistinguishable from a given spike train. The interval entropy is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…The stability of integrated XII th nerve activity from both wild type and Pet-1 −/− brainstem slices was assessed initially by plotting n versus n+1 Poincaré plots (Nayfeh and Balachandran, 1995;Garfinkel et al, 1997) of interburst interval (analogous to T E in vivo) from a 10 minute continuous recording, as described by Del Negro et al (2002). Subsequently, a measurement of the interval entropy (Reeke and Coop, 2004) was applied to the phasic network XII th nerve to quantify variability in the respiratory timing signal.…”
Section: In Vitro Hypoglossal Nerve Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of integrated XII th nerve activity from both wild type and Pet-1 −/− brainstem slices was assessed initially by plotting n versus n+1 Poincaré plots (Nayfeh and Balachandran, 1995;Garfinkel et al, 1997) of interburst interval (analogous to T E in vivo) from a 10 minute continuous recording, as described by Del Negro et al (2002). Subsequently, a measurement of the interval entropy (Reeke and Coop, 2004) was applied to the phasic network XII th nerve to quantify variability in the respiratory timing signal.…”
Section: In Vitro Hypoglossal Nerve Activitymentioning
confidence: 99%
“…The Poincarè analysis suggested that the timing of successive XII th nerve discharges were poorly correlated in the Pet-1 −/− slices. We used interval entropy analysis (Reeke and Coop, 2004) to quantify and compare the variability of interburst intervals in the respiratory neural network between genotypes. This analysis demonstrated that the inter-burst intervals between XII th nerve discharges were significantly more variable in Pet-1 −/− than wild type slices (Fig.…”
Section: Irregular Central Respiratory Rhythm In Pet-1 −/− Neonatesmentioning
confidence: 99%
“…Because calculating information content in neurophysiological data can encounter problems related to the sizes of temporal bins that are chosen, methods for calculation that include the construction of vector spaces and the estimation of interval entropy from an analytic distribution, methods that avoid bins, have been introduced (24)(25)(26). Additionally, information calculations are not restricted to single neuron action potential sequences and can be applied to sets of firing neurons (27).…”
mentioning
confidence: 99%
“…In particular, we previously found that an analytic methodology for quantifying the interval entropy of neuronal discharge gave considerable insight into the characteristics of patterns of neuronal discharge (13). We have recently extended this methodology to analyze the spatiotemporal and velocity components of the experiment reported here.…”
Section: Discussionmentioning
confidence: 92%